Variation of Tensile Strength and Cell Wall Component of Four Bamboos Species - Nareworo Nugroho; Effendi T Bahtiar; Dwi P Lestari; Deded S Nawawi (Masyarakat Peneliti Kayu Indonesia, 2013)
Bamboo is an alternative material of timber for building construction and furniture. The information of basic characteristic of bamboo is very important regarding to effective utilization of bamboo. This research aims to evaluate the variation of tensile strength and its relation to chemical cell wall component of bamboos. Four bamboos species namely andong (Giganctochloa psedoarundinaceae), betung (Dendrocalamus asper), mayan (Gigantochloa robusta), and tali (Gigantochloa apus) bamboos were subjected to analysis of its hollocellulose, cellulose, lignin, and tensile strength. Bamboo samples were taken from internode and node of middle section of bamboos stem.The results showed that the tensile strength of bamboo was influenced by chemical components of cell wall. The high content of alpha-cellulose and lignin contributed to high tensile strength of bamboo. Internode section of bamboo stem exhibited to have a higher tensile strength compared to node section.Key words: alpha cellulose, bamboo cell wall components, lignin content, tensile strength